Drinking Goal Trajectories and Their Association with Client Characteristics and Outcomes among Clients in Outpatient Alcohol Treatment. (10th November 2018) - Haug, Severin; Castro, Raquel Paz; Eggli, Peter; Schaub, Michael P.
ABSTRACT: Background : Drinking goal preferences could change over time in alcohol treatment and during follow up. Objectives : To examine the stability of drinking goals over time, types of drinking goal trajectory, and the associations between drinking goal trajectories and baseline client characteristics and treatment outcomes. Methods : We performed secondary analysis of a dataset from a multicenter longitudinal study on the effectiveness of outpatient alcohol treatment (n = 543). Drinking goals (abstinence, controlled drinking, nonrestricted drinking, undecided) and alcohol use were assessed at treatment admission, discharge, and 6- and 12-month follow up. Results : At admission, 32% of the subjects aimed for abstinence and 57% for controlled drinking, while 10% were undecided, and 1% did not want to restrict themselves. The proportions of clients aiming for abstinence and controlled drinking were relatively stable across the four assessments, and the proportion of clients who changed their drinking goal from abstinence to controlled drinking did not differ significantly from the number who changed in the opposite direction. Clients with abstinence-focused trajectories reported higher baseline alcohol use than those focused primarily on controlled drinking. Meanwhile, attaining nonhazardous drinking and reduced alcohol use at 12-month follow up were more likely among clients with abstinence-focused trajectories than those focused on controlled drinking. Conclusions : Since the majority of clients maintain their initially selected drinking goal, counsellors might inform them at treatment admission about the various probabilities of achieving nonhazardous drinking depending on their selected drinking goal.